Therapeutic Potential of Malaysian Stingless Bee Propolis Extract Targeting Macrophages in Atherogenesis: A Review: Therapeutic Potential of Malaysian Stingless Bee Propolis Extract - Aziz, Mohd Yusmaidie; Omar, Eshaifol Azam; Zulkafli, Nor Effa Syazuli; Mohamed, Rafeezul (Journal of Tropical Life Science, 2024)
Propolis is a sticky substance that originates from the collection of plant saps and resins by stingless bees. The bees blend this material with pollen and wax flakes, and their salivary fluids combine with the mixture to produce a potent compound that contains various chemical constituents, such as flavonoids and phenolic compounds. Numerous studies have revealed that propolis from stingless bees displays anti-inflammatory, antioxidant, immunomodulatory, and cardioprotective properties. Geniotrigona thoracica is one of the Malaysian stingless bee species, and propolis from this species is composed of a wide array of biochemical compounds and antioxidant properties that may have an anti-atherogenic effect. This review highlights the possible role of propolis from the Malaysian stingless bee G. thoracica as a macrophage-targeted therapeutic in atherogenesis, as macrophage-derived foam cell formation is integral to the development of atherosclerosis. The review first describes the characteristics, chemical content, and antioxidant properties of propolis from G. thoracica. It then discusses the pathogenesis of atherosclerosis, with a focus on macrophage-derived foam cell formation. Subsequently, the anti-atherosclerotic effects of propolis from G. thoracica are presented, and recent studies on the anti-atherosclerotic effects of propolis from honeybees worldwide are summarized for comparison. Finally, future perspectives are emphasized, highlighting the knowledge gaps that need to be investigated by researchers in this field.